2013
DOI: 10.7150/ijms.5753
|View full text |Cite
|
Sign up to set email alerts
|

Association of Increased Arterial Stiffness and P Wave Dispersion with Left Ventricular Diastolic Dysfunction

Abstract: Background: The association between increased arterial stiffness and left ventricular diastolic dysfunction (LVDD) may be influenced by left ventricular performance. P wave dispersion is not only a significant determinant of left ventricular performance, but is also correlated with LVDD. This study is designed to compare left ventricular diastolic function among patients divided by brachial-ankle pulse wave velocity (baPWV) and corrected P wave dispersion (PWDC) and assess whether the combination of baPWV and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Therefore, LV long-axis shortening and GLS may be reduced when pulling against a stiffer aorta because of a potential mechanical ventricular-vascular interaction. Both increased aortic stiffness and impaired GLS have been associated with impaired LV diastolic function in previous studies 12,19,34,35,38,[42][43][44][45][46][47] as well as in our cohort. 48 The relation between aortic stiffness and diastolic function is often attributed to hemodynamic effects, while the relation between GLS and diastolic function has been attributed to recoil of contracted LV muscle fibers.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, LV long-axis shortening and GLS may be reduced when pulling against a stiffer aorta because of a potential mechanical ventricular-vascular interaction. Both increased aortic stiffness and impaired GLS have been associated with impaired LV diastolic function in previous studies 12,19,34,35,38,[42][43][44][45][46][47] as well as in our cohort. 48 The relation between aortic stiffness and diastolic function is often attributed to hemodynamic effects, while the relation between GLS and diastolic function has been attributed to recoil of contracted LV muscle fibers.…”
Section: Discussionsupporting
confidence: 78%
“…Increased aortic stiffness has been linked to impaired LV systolic function, particularly along the LV long axis. [34][35][36][37][38][39] The relation is often attributed to increased hemodynamic load imposed by stiffer arteries. 36,40 However, our observed relations between aortic stiffness measures and GLS persisted after adjusting for traditional measures of hemodynamic load.…”
Section: Discussionmentioning
confidence: 99%
“…The association between arterial stiffness and LV diastolic function has been investigated in many studies. Although arterial stiffness has been assessed using different methods, such as aortic dimension and strain on echocardiography, the pulse pressure method, and baPWV, the close relationship between LV diastolic function and arterial stiffness is consistent among studies. A recent study performed by our group demonstrated an independent association between baPWV and global longitudinal strain of LV, supporting the evidence that increased arterial stiffness may result in impaired LV longitudinal function .…”
Section: Discussionmentioning
confidence: 98%
“…Carotid-femoral PWV has also been shown to be useful in identifying preclinical LVDD that outperformed central and brachial pulse pressure [39]. Tsai et al [40] examined a group of patients with suspected coronary artery disease, heart failure, hypertension, abnormal cardiac physical examination, survey for dyspnea and the pre-operative cardiac function survey. He has proven that patients with higher brachial-ankle PWV had higher prevalence of LVDD.…”
Section: Impact Of Arterial Stiffness On Lvddmentioning
confidence: 99%